Like tears in rain - Tur Planells, Helena (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The hybridization between organic and inorganic produces a sinister emotion In the cyborg, the organic part claims its place in humanity, but we fail to grant it. Except in one case: that of Roy Baty, the Nexus–6 replicant of Do Androids Dream of Electric Sheep? and its film adaptation Blade Runner. In this article, we are going to find out why.
Keywords: sinister; replicant; cyborg; antrhopogenesis